2014
DOI: 10.1371/journal.pone.0101131
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Methods Reporting in Parasitology Experiments

Abstract: There is a growing concern both inside and outside the scientific community over the lack of reproducibility of experiments. The depth and detail of reported methods are critical to the reproducibility of findings, but also for making it possible to compare and integrate data from different studies. In this study, we evaluated in detail the methods reporting in a comprehensive set of trypanosomiasis experiments that should enable valid reproduction, integration and comparison of research findings. We evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 126 publications
(61 reference statements)
0
22
0
Order By: Relevance
“…A recent report which examined the quality of sex-specific reporting in animal trypanosomiasis experiments found that despite known sex differences in mice with trypanosomiasis, only 70 % of the studies reported the sex of animals used in the experimental infection, and fewer (25 %) of the studies reported the sex of animals used to maintain their parasite stocks (Fl orez-Vargas et al, 2014). Similar omissions in other diseases are evident in the literature (Beery and Zucker 2011).…”
Section: Recommendationsmentioning
confidence: 92%
“…A recent report which examined the quality of sex-specific reporting in animal trypanosomiasis experiments found that despite known sex differences in mice with trypanosomiasis, only 70 % of the studies reported the sex of animals used in the experimental infection, and fewer (25 %) of the studies reported the sex of animals used to maintain their parasite stocks (Fl orez-Vargas et al, 2014). Similar omissions in other diseases are evident in the literature (Beery and Zucker 2011).…”
Section: Recommendationsmentioning
confidence: 92%
“…Most biomedical research journals, however, endorse ARRIVE but do not require completion of a checklist. Despite endorsement, however, subsequent surveys revealed that many published articles still lack key information required by ARRIVE (811) .…”
Section: Animal Research: Reporting In Vivo Experiments (Arrive)mentioning
confidence: 99%
“…In 2013, the United States FDA recommended lower doses of insomnia drugs for women than men (FDA 2013). Drugs containing zolpidem, in particular, remain in circulation longer, take longer to metabolize, and result in a longer duration of impairment of mental alertness in women compared with men.…”
Section: Studying Sex Differences Saves Lives and Moneymentioning
confidence: 99%
“…Drugs containing zolpidem, in particular, remain in circulation longer, take longer to metabolize, and result in a longer duration of impairment of mental alertness in women compared with men. The FDA cut the recommended dose of sleep medications that contain zolpidem in half for women (FDA 2013). Media outlets extensively reported this story as novel and newsworthyprimarily on the basis that drugs may need to be administered with sex-specific dosage recommendations.…”
Section: Studying Sex Differences Saves Lives and Moneymentioning
confidence: 99%